Microbial community and metabolic responses to electrical field intensity for alleviation of ammonia inhibition in an integrated bioelectrochemical system (BES). (September 2021) - Wang, Han; Zheng, Xiaoxiao; Yan, Qun; Zhang, Guangsheng; Kim, Jung Rae
Graphical abstract: Highlights: Ammonia inhibition could be alleviated in the integrated BES under 0.2 V. Hydrogenotrophic methanogens seemed to be more robust to high voltages. Some bacteria for hydrolysis and acidogenesis were vulnerable to high voltages. Metabolic pathways of substrates degradation were inhibited at high voltages. Enzymes for all steps of AD process were affected by different applied voltages. Abstract: Bioelectrochemical system (BES) is a promising solution for mitigation of ammonia inhibition in anaerobic digestion (AD) process. However, the effect of electric field intensity on microbial community changes and metabolic function prediction during the alleviation of ammonia inhibition are still missing. The results of the current study represented that the improvement of ammonia removal (20.6%) and methane production (14.6%) could both be achieved at 0.2 V while higher voltages led to reductions of methane production (more than 48.9%) compared with the control. Moreover, hydrogenotrophic methanogens ( Methanobacterium ) seemed to be more robust to high voltages compared with aceticlastic methanogens ( Methanosaeta ). Additionally, bacteria for hydrolysis and acidogenesis ( Rikenellaceae and Soehngenia ) were found vulnerable to external electric field intensity. Furthermore, abundances changes of metabolic pathways demonstrated that the degradation of carbohydrates, lipids and proteins during all steps (hydrolysis, acidogenesis, acetogenesis and methanogenesis) of AD process could be affected by different applied voltages.